Real-Time Emulsified Fuel Supply Systems: Effects on Diesel Engine Emissions - H.A. Hassan; N. Aliman; M.A.H. Hafiezal (Journal of the Society of Automotive Engineers Malaysia, 2025)
Diesel engines are widely used because of their fuel efficiency in producing a higher mechanical energy ratio compared to gasoline engines. The emulsification technology called the Real-Time Emulsified Fuel Supply System (RTES) has been developed to produce fresh emulsified fuel and eliminate the need for additives like surfactants. The goal of this study is to quantify fuel usage and look at the vehicle's diesel engine's emissions of dangerous gases, including carbon monoxide (CO), nitrogen oxides (NOx), and smoke opacity. The RTES has a rotary blade to improve the efficiency of emulsified production by continuously mixing the oil and water phases during processing. Experiments were conducted on a dynamometer using emulsified diesel fuels containing 10% water by volume. Emission tests were performed on a Nissan Navara at idle, with engine speeds ranging from 800 to 2000 rpm. The findings indicate that emulsified fuel provides notable benefits in lowering NOx emissions and smoke opacity compared to conventional diesel fuel, especially at elevated engine speeds. However, it also tends to raise CO emissions under these conditions. Emulsified fuel presents a viable method to mitigate harmful emissions from diesel engines and serves as an effective alternative for reducing NOx and smoke, particularly in high-speed engines, delivering optimal environmental outcomes.